Coping with adverse childhood experiences during the COVID-19 pandemic: Perceptions of mental health service providers - Choudhury, Sumaita; Yeh, Paul G.; Markham, Christine M. (Frontiers in Psychology, 2022)
Background: Adverse Childhood Experiences (ACEs) have been associated with long-term physical and mental health conditions, toxic stress levels, unstable interpersonal relationships, and substance use disorders due to unresolved childhood adversities. Aims: This study assessed the perspectives of mental health providers (MHPs) regarding their adult patients’ coping with ACEs during COVID-19 in Houston, Texas. Specifically, we explored how individuals with ACEs are coping with the increased stresses of the pandemic, how MHPs may provide therapeutic support for individuals with ACEs during this pandemic, pandemic-related challenges of accessing and utilizing mental health services for individuals with ACEs, and the awareness and treatment of ACEs among MHPs. Methods: Ten in-depth semi-structured virtual interviews were conducted with licensed MHPs from November 2021 to April 2022 in Houston, Texas. Interviews were coded and analyzed for emerging themes through an inductive open coding approach to discover insights regarding coping with ACEs during COVID-19. Results: Four key themes experienced by individuals with ACEs emerged from the MHP interviews: (1) Maladaptive emotional dissonance and coping outlets during the pandemic, (2) Difficulties with social connectedness and significance of social support, (3) Heightened daily life stressors and coping with the ongoing disruption of the pandemic, and (4) Changing interactions with the mental health system. Themes from this study highlighted that resilience, seeking treatment, and strong social support can help develop healthy coping strategies among individuals with ACEs. Conclusions: This study may help inform efforts during a persistent pandemic and an uncertain future to develop interventions and policies regarding ACEs across vulnerable populations.